Ethics and politics in school leadership : finding common ground - Brierton, Jeffrey T. (Concordia University Chicago leadership series., 2016)
"The authors are national school resource experts and have teamed up to write a comprehensive book on ethics and politics. It covers everything you need to know about ethical leadership and dealing with politics in schools. The book starts with an ethical framework and moves on to politics with unions, administrators, and School Boards with suggested strategies for effective conflict resolution. There are realistic cases in every chapter of the book with the final chapter focused on comprehensive ethical and political cases to test the reader in addressing such issues in the educational or related settings."--